Haarzellleukämie = ResterkrankungHairy cell leukemia - Dietrich, Sascha; Andrulis, Mindaugas; Zenz, Thorsten (Der Internist, 2015)
Hairy cell leukemia was initially described as a distinct entity in 1958. It is rare B-cell malignancy characterized by an indolent course. Advances in the treatment and understanding of the biology of hairy cell leukemia have made the disease exquisitely amenable to treatment. This review summarizes the present understanding of hairy cell leukemia with a particular focus on the development of novel and targeted approaches to treatment.
Gesehen am 21.07.2017